Simulation of water resource development and environmental flows in the Lake Tana Sub basin - Alemayehu, T.; McCartney, Matthew P.; Kebede, S. (2009)
Lake Tana is a natural reservoir for the Blue Nile River which has huge potential for hydropower and irrigation development. Water resource development is being encouraged by the government to stimulate economic growth and reduce poverty. In this study, the Water Evaluation And Planning (WEAP) model was used to simulate planned hydropower and irrigation development scenarios. Simulation of water demand and estimated downstream environmental flows was conducted for a 36-year period of varying flow and rainfall. Based on the simulation results, water availability for the different proposed irrigation and hydropower schemes was determined. The likely impact of future water resource development on water levels of the lake was assessed based on the simulation results of three development scenarios. The simulation results revealed that, if the full future development occurs, on average, 2,207 GWhy-1 of power could be generated and 548 Mm3y-1 of water could be supplied to irrigation schemes. However, the mean annual water level of the lake would be lowered by 0.33 meters (m) with a consequent decrease of 23 km2 in the average surface area of the lake. Besides having adverse ecological impacts, this would also have significant implications for shipping and the livelihoods of many local people.